The Never-Ending Story Teller – A Narratological Genealogy of Storytelling in Marketing and Management - König, Jan C. L. (International Review of Management and Marketing, 2020)
Storytelling has become remarkably important in marketing and in numerous other areas in the discipline of management and organization studies. While recent studies have only focussed on details, narratological theories, unlike other popular approaches, offer the chance to observe storytelling from a structuralist or functionalist view as a systematic phenomenon that follows specific rules. These basic rules can be combined in a step-by-step blueprint that permits the creation and advancement of stories that pertain to the needs of marketing and management. In this research, the most important aspects of narrative theory have been compiled, from literature and language studies of the post pragmatic turn with modern ideas regarding screenwriting, archetypal characters, and brand management. The results reflect the need to develop a concept that can detect major problems with coherent storytelling. While storytelling has become of major interest in marketing and management, the phenomenon has not been sufficiently discussed from the perspective of narrative theory, the field in which it is originally rooted. Hence, many specific story elements have not been examined. This article collects the most important approaches to framework stories and consequently presents the possibility of creating a concept of storytelling based on narrative elements, with both contributions to further research and practical implications. Keywords: Story Teller, Narratological Theories, Marketing, Management JEL Classifications: M1, M31 DOI: https://doi.org/10.32479/irmm.10187